2023
DOI: 10.23822/eurannaci.1764-1489.268
|View full text |Cite
|
Sign up to set email alerts
|

Posterior nasal nerve neurectomy for the treatment of rhinitis: a systematic review and meta-analysis

Abstract: BackgroundPosterior nasal nerve neurectomy (PNNN) is a surgical option for the treatment of refractory chronic rhinitis. It can be performed by surgical dissection, cryotherapy, or laser ablation. ObjectiveThis systematic review aimed to assess the effect of PNNN on Total Nasal Symptom Score (TNSS) in adults with chronic rhinitis. MethodsA systematic review of EMBASE, MEDLINE, PubMed and ClinicalKey databases was conducted in November 2021. Studies reporting PNNN performed as a single procedure in adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…60,61 Studies, such as that PNN requires us to find and separate the posterior nasal neurovascular bundle at the posterior end of the middle turbinate, and then use bipolar electrocoagulation or plasma knife to coagulate and cut off the posterior nasal nerve. 9 The posterior nasal nerve is mainly composed of sensory fibers of the maxillary nerve and post-pterygonomic fibers of the sphenopalatine ganglion, which contain sympathetic and parasympathetic components. PNN simultaneously cuts off the branches of the sympathetic, parasympathetic, The anterior ethmoid nerve is derived from the ophthalmic nerve, 62 which is a mixed nerve of sensory and parasympathetic nerve, and its main branches innervate the anterior nasal cavity and sinus mucosa.…”
Section: Response Rate In Allergic Rhinitis Combined With Chronic Rhi...mentioning
confidence: 99%
See 1 more Smart Citation
“…60,61 Studies, such as that PNN requires us to find and separate the posterior nasal neurovascular bundle at the posterior end of the middle turbinate, and then use bipolar electrocoagulation or plasma knife to coagulate and cut off the posterior nasal nerve. 9 The posterior nasal nerve is mainly composed of sensory fibers of the maxillary nerve and post-pterygonomic fibers of the sphenopalatine ganglion, which contain sympathetic and parasympathetic components. PNN simultaneously cuts off the branches of the sympathetic, parasympathetic, The anterior ethmoid nerve is derived from the ophthalmic nerve, 62 which is a mixed nerve of sensory and parasympathetic nerve, and its main branches innervate the anterior nasal cavity and sinus mucosa.…”
Section: Response Rate In Allergic Rhinitis Combined With Chronic Rhi...mentioning
confidence: 99%
“…PNN selectively cuts off the nerve branches distributed in the nasal cavity, so the postoperative pain response is smaller and the surgical complications are less. 9 At present, a large number of experiments have shown that the above surgical methods can improve AR, 10 but there is no gold standard procedure for the treatment of allergic rhinitis. 11 In this study, network meta-analysis was used to study the differences in the efficacy of different surgical methods and to evaluate them, so as to provide a reference for clinicians in the choice of surgical methods for allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review by Balai et al, which evaluated the efficacy of these minimally invasive procedures, showed that these treatments improved chronic rhinitis symptoms. 6 However, only one of their eight studies examined the effects of radiofrequency ablation of the PNN. Since the publication of this systematic review, neurolysis of the PNN with temperature-controlled radiofrequency has been gaining more interest.…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review by Balai et al, which evaluated the efficacy of these minimally invasive procedures, showed that these treatments improved chronic rhinitis symptoms 6 . However, only one of their eight studies examined the effects of radiofrequency ablation of the PNN.…”
Section: Introductionmentioning
confidence: 99%
“…The newly updated Chinese guidelines of allergic rhinitis [1,2] have introduced that type 2 innate lymphoid cells (ILC2) function in type 2 immune responses during early allergic rhinitis and highlighted the crucial regulatory roles played by type 2 follicular helper T cells (Tfh) and follicular regulatory T cells (Tfr) in the production of IgE and the pathogenesis of allergic rhinitis, reflecting an innovative understanding of the mechanism of allergic rhinitis driven by basic immunological findings and providing a theoretical basis for further research. Additionally, the newly updated guidelines have stressed that substance P and calcitonin gene-related peptides (CGRP), which are secreted by nerve fibers around the nasal mucosal glands, increase significantly during allergic rhinitis and are closely involved in airway hyperresponsiveness [9,10], providing a theoretical justification for the clinical treatment of allergic rhinitis through parasympathetic nerve dissection using a minimally invasive endoscopic approaches [11,12].…”
Section: Introductionmentioning
confidence: 99%